Efficiency of short-grain rice breeding program between pedigree and single seed descent methods for yield, biotic resistance and cooking quality derived from indica × japonica - Thongyos, Peeranut; Narumol, Possawat; Saichompoo, Uthomphon; Cheabu, Sulaiman; Ittisoponkul, Teerarat; Pornprom, Tosapol; Chai-Arree, Witit; Malumpong, Chanate (Agriculture and Natural Resources, 2023)
Importance of the work: Japanese food is popular in tropical countries; however, high-yielding and good-quality temperate japonica rice supplies are limited in tropical climates. Objectives: To compare two breeding methods: pedigree and single seed descent applied for a short-grain rice (japonica-like) breeding program. Materials & Methods: A temperate japonica rice (Koshihikari) and a tropical indica fragrant rice (Pathumthani1) were used as parents. The pedigree and single seed descent methods were used to select breeding lines from F2 to F5. Preliminary yield trials and yield traits of selected breeding lines were investigated in F5 to F7. Results: From the preliminary trial, based on short-grain, plant type and grain yield criteria, two breeding lines (PS171-31-10 from the pedigree method and SSD125-7 from the single seed descent method) were selected in which genetic markers for bacterial leaf blight resistance (Xa21) and blast resistance (Pi-ta) were detected. In the yield trial experiments, the mean grain yields of PS171-31-10 (5.07±3.46 t/ha) and SSD125-7 (4.43±3.00 t/ha) were higher than those of the japonica parent (4.30±1.99 t/ha) but lower than those of the indica parent (5.80±1.17 t/ha). In addition, the highest overall scores of sensory tests were for Ps-171-31-10 (37.58 overall score), the second highest was for SSD-125-7 (35.37 overall score), while Koshihikari had the third highest sensory score. The physical and chemical properties of the milled grain from the two lines were consistent with standard japonica rice. In addition, the badh2 gene was detected in SSD125-7, which is identified as a japonica fragrant rice variety. Main finding: The pedigree and single seed descent methods created new short-grain varieties with comparable performance: adaptability to tropical environments, production of satisfactory grain yields and good cooking quality, similar to that of japonica rice.